Mel da cana de açúcar é tão efetivo quanto suplementação semanal de ferro na prevenção e tratamento de anemia em pré-escolares - Freire, Cecília Costa Arcanjo (2021)
Iron deficiency anemia remains a serious public health problem worldwide. This condition assumes greater importance in the case of preschool children, as it is a period of maximum demand for this nutrient and because it results in neurodevelopmental and cognitive deficits, justifying the search for low-cost, sustainable and accessible alternatives to address this condition. Objective: To compare the effect of sugar cane honey, ferrous sulfate oral solution and control on hemoglobin concentrations, and anemia prevalence in preschoolers. Methods: In a cluster-randomized clinical trial, we evaluated preschoolers aged 24-36 months. Intervention lasted 16 weeks. Children were cluster randomized to either sugar cane honey once daily (group A), 6mg/kg elemental iron once weekly (group B), or control (Group C). Primary outcome variables were change in hemoglobin concentration and anemia prevalence. Two biochemical evaluations were performed before and after intervention to determine hemoglobin concentrations. Results: Group A: at baseline mean hemoglobin concentration was 11.10±1.29g/dL and 11.60±0.72g/dL after intervention, p=.002; 12 out of 21 participants who were anemic at baseline had normal Hb levels after intervention. Relative risk (RR)=0.63, number needed to treat (NNT)=2. In group B, mean baseline hemoglobin was 11.19±1.42g/dL, and 12.04±0.96g/dL after intervention, p=.0003; 16 out of 20 participants who were anemic at baseline had normal Hb levels after intervention. RR=0.36, NNT=2. In the control group mean baseline hemoglobin was 11.85±0.86g/dL, decreasing to 11.11±0.87g/dL after intervention, p<.0001 with an increase in the number of anemic individuals. Conclusion: Sugar cane honey was as effective as weekly iron supplementation to prevent and treat anemia in preschoolers